Toward a Normative Model of Promotional Decision Making - Aaker, David A. (Management Science, 1973)
This paper presents a normative model of promotional decision making and reviews current literature in the model context. The model emphasizes the long-run impact of promotions and draws upon stochastic buyer-behavior model technology. In particular, a stochastic model is used to predict the level of brand acceptance obtained from a group of new triers attracted by a promotion—consumers with no recent use experience with the brand. This brand acceptance is made a function of the composition of the new-trier group. Finally, attention is focused upon the probability distribution of those attracted by the promotion, conditional on the nature of the promotion. This distribution is used to develop expressions for the expected long-term worth of a new-trier group attracted by a specific promotion.